Multinational Tax Planning: Foreign Tax Credit Limitations And Income Shifting - Putri, Mareta; Sihombing, Belandina Anita Sere; Fuadah, Luk Luk (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study analyses the influence of Foreign Tax Credit (FTC) Limitations and Income Shifting on the taxation strategies of multinational companies using the Systematic Literature Review (SLR) method. This study categorises findings from 20 scientific articles into three main groups: research supporting the significant influence of FTC Limitations and Income Shifting on tax strategies, research finding no strong relationship between the two, and research identifying other factors contributing to multinational companies' tax planning. The results indicate that FTC Limitations encourage companies to use Income Shifting strategies to reduce their global tax liabilities. Practices such as transfer pricing, thin capitalisation, and the use of tax havens are often used to optimise tax payments. However, some studies indicate that domestic tax policies, corporate ownership structures, and international accounting standards also play an important role in corporate tax decisions. In addition, the lack of coordination in tax policies between countries creates loopholes that allow companies to exploit tax arbitrage